ICT Innovation Strategy in Malaysia Public Research Institutes and Government Agencies - Irny, Suzila Ishak; Rose, Alinda Alias; Izwan, Suhadak Ishak; Zurinah, Suradi (2013)
Information and Communication Technology (ICT) play important roles within the rapid growth of innovation environment. The roles include as a change agent, enhancing e-business requirements, promoting globalization and innovation, contributing to productivity growth, strengthening competitiveness, improving business processes along the whole value chain, determining future business strategies and generating profits for business. Previous studies have shown that by adopting ICT, the organization will attain positive impacts of innova-tion especially in product innovation, process innovation and competitive advantage. This indicates that ICT has significantly contributed to-wards promoting innovation in the organization. This paper presents the results of the study of ICT innovation in Malaysian Public Research Institute and Government Agencies (IPA). The study focuses on existing ICT strategies that promote innovation in IPA. Data was collected through questionnaires which were distributed to the selected Heads of IT Division in IPA. The findings of the study shows ICT innovation helped IPA in areas of creativity, product development, capacity development and strategic. This research also shows that IPA produced several ICT strategic applications for promoting innovation derived from ICT Strategic Plan (ICTSP). This research will help other research institutes to learn from each other and practice innovation in their organization.